The Student-to-staff partnership experience in a university-based humanitarian organization - Ungras, Oshish (International Journal for Students as Partners, 2024)
My journey of student-faculty partnership is one that I did not anticipate joining when I signed up for the International Students Overcoming War (ISOW) Scholarship Initiative. ISOW is part student-club, part humanitarian organization that provides students the opportunities to hone their leadership skills as they administer the operations of the scholarship program. The partnerships between students, staff, and Faculty create (experiential) learning for all that enhances personal and professional development in this community. Over the course of four years, with progressive leadership responsibilities ranging from Secretary to a full-time contract position, I have been able to experience partnership from the student and staff perspective. In this essay I share the key lessons I have learned about partnership as I moved through these roles and experienced the challenges of self-reflection, holding multiple identities, and moving on.